Vpliv visokotemperaturnega lezenja jekla na požarno odpornost vijačenih jeklenih konstrukcijskih sistemov - Češarek, Peter (Gradbeni vestnik, 2018)
The article presents computational results of the influence of high temperature creep on the mechanical response of bolted steel structural systems during fire and simultaneously compares two approaches to modelling creep of steel in a numerical analysis: (i) the simpler approach where creep strains are integrated implicitly in the plasticity model (such as, for example, the approach proposed by EN 1993-1-2, 2004) and (ii) the more consistent approach where creep strains are considered separately, i.e. explicitly. In everyday engineering applications, the first approach is most often applied, however it is alarming to observe that the limits of its validity are thereby often overlooked. So far, the severity of the consequential error of the results of such applications has been investigated for individual structural members (e.g. beams, columns). This paper, however, presents such comparison for bolted structural assemblies. With these, as the paper reveals, the influence of creep is most pronounced in the between-member connections. The results show that the times of structural failure predicted by the implicit-creep plasticity model are significantly longer than failure times predicted by the explicit creep model, if the implicit model is applied outside the limits of its applicability. Even more disturbing, however, is the finding that for one of the explored steels such differences are found also within these limits.
Keywords: civil engineering; creep; fin plate connections; fire; gradbeništvo; jeklene konstrukcije; lezenje; ovirane deformacije; požari; restrained beams; steel structures; vijačeni spoji